Retrospective study of thalidomide plus dexamethasone versus conventional chemotherapy in the relapsed multiple myeloma patient and the study of melphalan and prednisone versus melphalan, prednisone, and thalidomide (Hematology Meeting Reports, 2009)
Thalidomide shows promise in the treatment of multiple myeloma (MM). Questions remain, however, about its efficacy compared with conventional chemo-therapy.